Development and evaluation of a general-purpose electric off-road robot based on agricultural navigation - Xiang, Yin; Noguchi, Noboru (International Journal of Agricultural and Biological Engineering, 2014)
The aim of this study was to develop a general-purpose electric off-road robot vehicle by using automatic control technologies. The vehicle prototype used in this study was a commercially-purchased electricity utility vehicle that was designed originally for manual operations. A manipulating unit, an automatic steering system and a speed control system were developed and integrated into a CAN-bus network for operating on functions (forward, reverse, park or stop), realizing desired steering angles and maintaining a constant speed, respectively, in the mode of automation. An autonomous navigation system based on RTK-GPS and IMU was used to evaluate the performance of the newly developed off-road robot. Field tests showed that the maximum error in speed control was 0.29 m/s and 0.22 m/s for speed tests and autonomous runs, respectively. The lateral offset was less than 10 cm in terms of straight paths, indicating that the automatic steering control system was of good performance.Keywords: electric off-road robot, automatic control, automatic steering, speed control, autonomous navigation system, field testDOI: 10.3965/j.ijabe.20140705.002Citation: Yin X, Noguchi N. Development and evaluation of a general-purpose electric off-road robot based on agricultural navigation. Int J Agric & Biol Eng, 2014; 7(5): 14－21.